Responses of the wintertime auroral E-region neutral wind to varying levels of geomagnetic activity - Zhan, Weijia; Keappler, Stephen R. (Frontiers in Astronomy and Space Sciences, 2023)
We conduct a statistical examination of the reactions of wintertime neutral winds to four various degrees of geomagnetic activity, with a focus on the impacts of ion drag. Neutral winds between 90-125 km derived from Poker Flat Incoherent Scatter Radar (PFISR) observations during the winters of 2010-2019 are collected and divided into four distinct groups based on the geomagnetic disturbance level indicated by the local magnetometer's measurements (∆H). We find that (1) when geomagnetic activity increases, dawn-dusk asymmetry exists in both zonal and meridional winds in the upper E regionE-region with stronger zonal wind in the dusk sector than in the dawn sector and much stronger meridional wind in the dawn sector than in the dusk sector. The dawn-dusk asymmetry in the zonal direction is consistent with previous research which suggests the role of gradient wind balance in the E regionE-region in leading to stronger neutral circulation in the dusk sector than in the dawn sector; the much stronger postmidnight interaction between tidal components with different phases, which could lead to the reduction or even inhibition of the zonal wind.